Development and Performance Evaluation of Biomass Pyrolysis System for Biofuel Production - Ndagi MAMUDU; Ibrahim S. MOHAMMED; Mohammed ALIYU; Peter DANIEL; Timothy Y. AKANDE; Bala A. GARBA (FUDMA Journal of Engineering and Technology, 2026)
Agricultural crop residues particularly groundnut shell, melon shell and shea nut shell are the main contributors to biomass waste in Nigeria. The mismanagement of these agricultural wastes has become a significant concern causing adverse environmental impacts and also poses a severe threat to soil health. A small capacity (10kg/batch) fixed bed pyrolizer was designed and fabricated for obtaining bio-fuel from these biomasses solid waste. The vertical fixed bed reactor with the dimensions of 600mm length and diameter 150mm was used in carrying out the experiments. The effect of feedstock composition, temperature (200 °C – 500 °C) and residence time (30-120 min) at constant feedstock mass of 500g per run was studied. Three main products were obtained; bio-char, bio-oil and bio-gas. The feedstock composition particle size of 1.18mm was used. The feedstock composition, temperature and residence were found to influence the products yield significantly. The maximum bio-char yield was 72.1 wt% at 200 °C with a residence time of 30 minutes. The maximum bio-oil yield was 43.5 wt% at 500 °C) with a residence time of 120 minutes. The maximum bio-gas yield was 43.4wt% at 500 °C with running time of 120 minutes. Also, the bio-char yield of 39.62 wt%, bio-oil yield of 17.61wt% and bio-gas yield of 41.22wt% at temperature and residence time of 388.07 °C and 113.785 minute respectively, resulted in optimum bio-fuel yield having maximum desirability of 1. The reactor efficiency which was evaluated at various temperatures gave maximum efficiency of 60.8%. This indicate that, the reactor is efficient enough to produce bio-oil. Hence, the result obtained contributes to improving mismanagement of agricultural waste that cause adverse environmental impacts.
Keywords: Pyrolysis, biomass, bio-char, bio-oil and bio-gas.